Dietary and physical activity behaviors among adults successful at weight loss maintenance - Gillespie Cathleen; Blanck Heidi; Kruger Judy (BMC, 2006)
Abstract Background There is limited population-based data on behavioral factors found to be important for successful weight loss maintenance among adults. Methods Data from the 2004 Styles surveys, mailed to U.S. adults aged ≥18 years were used to examine the difference in selected weight loss strategies and attitudes among persons who reported successful weight loss attempts (lost weight and able to keep it off) and persons who were not successful (previous attempts to lose weight were unsuccessful or they could not keep the lost weight off). Behaviors examined included modification of diet, leisure-time and sports activities, and self-monitoring, and barriers to weight management. Results Among adults who reported losing weight or trying to lose weight, 31.0% had been successful at both losing weight and maintenance after weight loss. Successful weight loss status differed by sex, age, and current weight status. Assessment of reported weight loss strategies, found that exercising ≥30 minutes/day and adding physical activity to daily life were significantly higher among successful versus unsuccessful weight losers. Individuals who were successful at weight loss and maintenance were less likely to use over-the-counter diet products than those who were unsuccessful at weight loss. Significantly more successful versus unsuccessful weight losers reported that on most days of the week they planned meals (35.9% vs. 24.9%), tracked calories (17.7% vs. 8.8%), tracked fat (16.4% vs. 6.6%), and measured food on plate (15.9% vs. 6.7%). Successful losers were also more likely to weigh themselves daily (20.3% vs. 11.0%). There were a significantly higher proportion of successful losers who reported lifting weights (19.0%) versus unsuccessful (10.9%). The odds of being a successful weight loser were 48%-76% lower for those reporting exercise weight control barriers were influencing factors (e.g., no time, too tired to exercise, no one to exercise with, too hard to maintain exercise routine) compared to those who reported little or no influence of exercise; similarly, the odds were 48-64% lower for those who found certain dietary barriers to be influential (e.g., eat away from home too often, diet/health food costs too much). Conclusion Self-monitoring strategies such as weighing oneself, planning meals, tracking fat and calories, exercising 30 or more minutes daily, and/or adding physical activity to daily routine may be important in successful weight loss maintenance. Leisure-time activities such as lifting weights or cooking/baking for fun are common strategies reported by those who were successful weight losers.